2019
DOI: 10.2174/1574888x13666181002151330
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6 (CD49f), The Microenvironment and Cancer Stem Cells

Abstract: Cancer is a highly prevalent and potentially terminal disease that affects millions of individuals worldwide. Here, we review the literature exploring the intricacies of stem cells bearing tumorigenic characteristics and collect evidence demonstrating the importance of integrin α6 (ITGA6, also known as CD49f) in cancer stem cell (CSC) activity. ITGA6 is commonly used to identify CSC populations in various tissues and plays an important role sustaining the self-renewal of CSCs by interconnecting them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Both of these integrins are cell adhesion molecules that are vital to signalling pathways that regulate tumour development, metastasis, and angiogenesis [38,39]. Several lines of evidence demonstrate that ITGA6 is a putative stemness marker [[40], [41], [42], [43]], and aberrant expression of ITGA6 has been shown to play an important role in the development and progression of various types of cancers [29,[44], [45], [46]]. Notably, the expression of ITGA6 is significantly associated with the incidence of intravesical recurrence [47].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these integrins are cell adhesion molecules that are vital to signalling pathways that regulate tumour development, metastasis, and angiogenesis [38,39]. Several lines of evidence demonstrate that ITGA6 is a putative stemness marker [[40], [41], [42], [43]], and aberrant expression of ITGA6 has been shown to play an important role in the development and progression of various types of cancers [29,[44], [45], [46]]. Notably, the expression of ITGA6 is significantly associated with the incidence of intravesical recurrence [47].…”
Section: Discussionmentioning
confidence: 99%
“…Blaber et al 8 also reported that multiple markers indicative of self-renewal of stem cells were increased under sµg. We previously identified integrin α6 (also known as CD49f and ITGA6) as a key regulator in the self-renewal of hPSCs 38 and as the only common stem cell-related protein expressed in all 35 identified stem cell types 39 , 46 . Here, we also observed that sµg upregulates the expression of pluripotent TFs and integrin α6 both at gene and protein levels in hPSCs in comparison to the 1g control group.…”
Section: Discussionmentioning
confidence: 99%
“…The integrin subunit a6 (coded by the gene ITGA6 ) has received considerable attention, especially for its role in regulating cancer stem-like cells [ 19 , 20 ]. Integrin a6 dimerizes with integrin b1 or b4 to generate the surface receptor for laminin.…”
Section: Introductionmentioning
confidence: 99%